Isolation of Indigenous Bacteria from Paddy Field for Methomyl Degradation - W Wartono; RA Suwignyo; A Napoleon; Suheryanto Suheryanto (Jurnal Ilmu Alam dan Lingkungan, 2021)
Methomyl is an active ingredient of carbamate group pesticide. The uncontrolled application of methomyl may contaminate the water and soil. The objective of this research was to find indigenous bacteria that could degrade the methomyl. The soil samples were taken from the soil of the rice field located in Musi Rawas District, South Sumatera, Indonesia. The soil bacteria that were found to degrade methomyl were isolated by using a medium containing methomyl. There were 2 of 16 isolates that could grow in a high concentration of methomyl and they were Acinetobacter baumannii and Bacillus megaterium.